Partisipasi Masyarakat dalam Perencanaan Pembangunan Desa di Desa Warung Bambu Kecamatan Karawang Timur Kabupaten Karawang - Noviar, Idham; Priyanti, Evi (Universitas Indo Global Mandiri, 2023)
Development planning is a step that needs to be initiated by the Government in making a development policy. The purpose of this research was to produce an analysis related to the participation of the Warung Bambu Village Community regarding a development plan in Warung Bambu Village, Karawang Regency. This study uses a qualitative method using the theory of Sarah Cook and Steve Macaulay which consists of 4 indicators, namely decision making, implementation, satisfaction, and evaluation. Participation is indispensable in development planning. In planning for participatory development there are also clear criteria, including the involvement of all stakeholders, efforts to build strong and legitimized community institutions, the existence of a political process through negotiations or deliberations which ultimately leads to the formation of collective agreements with the principle of togetherness, and efforts community empowerment through joint learning activities as part of the democratization process. The results of the research include first, the Village Government in making decisions has carried out the Village Development Planning Meeting (MusRemBang), but it is only held once a year and does not directly involve the community but only representatives of each hamlet, namely the Hamlet Head; Second, the Village Government in realizing community involvement is still lacking because there is no forum for aspirations and the Village Information System (SID) via the website is still problematic; Third advantage received by the Government in Community involvement is still very less; And the fourth evaluation in reducing community participation in development planning is still a future plan.